Role of Caveolin-1 in Sepsis – A Mini-Review - Lannes-Costa, Pamella Silva; Pimentel, Bruna Alves da Silva; Nagao, Prescilla Emy (Frontiers in Immunology, 2022)
Sepsis is a clinical syndrome characterized by extreme response to an infection. In addition, because of the diverse manifestations of sepsis, clinicians continue to face serious challenges in diagnosing, treating, and managing patients with sepsis. In this mini-review we demonstrate recent developments on cellular pathogenesis and the role of Caveolin-1 (Cav-1) in sepsis. Studies have indicated that Cav-1 plays an important role in sepsis through the regulation of membrane traffic and cellular signal transduction. Moreover, accumulating evidence shows that apoptosis/autophagy activation influences the progression and development of sepsis in multiple ways. However, how Cav-1 is involved in sepsis remains unclear, and the precise mechanisms need to be further investigated. Finally, the role of Cav-1 in altering cell permeability during inflammation, in sepsis caused by microorganisms, apoptosis/autophagy activation and new therapies under study are discussed in this mini-review.